PENGEMBANGAN BAHAN AJAR MATEMATIKA DISKRET DENGAN PENDEKATAN BERBASIS MASALAH BAGI MAHASISWA PROGRAM STUDI TEKNIK INFORMATIKA DI STMIK ASIA MALANG - Hakim, Lukman; Habibi, Azwar Riza (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Hasyim Asy'ari (Unhasy), 2018)
AbstractThe present paper deals to develop the discrete mathematics module by approaching problembased learning problem in STMIK Asia Malang. Developing of module carried out on the modelintroduced by Plomp namely, preliminary research phase, prototype phase, development phase,and the assessment phase. Based on the problem based learning, we have three part sections onthe produc, there are the history, the material exposure, and the program implementationsection. Furthermore, from the results of testing the instructional material, we have a validityscore of 96.25%. In this case, it implies that the module hold on the eligible criteria withoutrevision. Then the part of practicality, we have the score test 88.75%, and the effectivenessmodule close to score 85.5%. From the results give us the information about the module byapproaching the problem based learning has to able to, and finally, the module implies thestudents to understand the material with the implementation program.Keywords: Discrete Mathematics, Module, Problem Based Learning, Informatics Engineering,Programming.